Design, construction and performance evaluation of the absorption type refrigerator (2004)
The absorption refrigerating mechanism is based on Dalton Law of partial pressure. The refrigerant is ammonia with hydrogen as the propellant. The unit comprises a generator, condenser, evaporator and absorber. Ammonia is driven out of the water in the boiler when heat is applied. In the condenser, it is liquefied and evaporates at low pressure in the evaporator. As the ammonia boils, it absorbs heat. The refrigerator is built entirely with locally available materials and functions on a kerosene burner. It is a viable alternative to the conventional compressor-type refrigerator and in addition avoids the hazards associated with the conventional refrigerants.